(untitled) (Third Sector Social Economic Review, 2012)
The purpose of this paper is to examine the influence of assigned and aspirational role models on the buying intentions and buying behavior of college students. Data were obtained from a survey sample of 173 students, aged 18-23 years, from two universities in Ankara, Turkey. Assigned role models (parents) were determined to be influential in the buying intentions and behavior of the students; whereas athletes and celebrities were influential only over the buying behavior. Since Turkish culture is a collectivist one, it is expected that personal and celebrityoriented social relations play an important role in the buying intentions and behavior of young consumers.